2020
DOI: 10.1038/s41598-020-66672-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the genetic architecture of depression

Abstract: The prevalence and clinical characteristics of depressive disorders differ between women and men; however, the genetic contribution to sex differences in depressive disorders has not been elucidated. To evaluate sex-specific differences in the genetic architecture of depression, whole exome sequencing of samples from 1000 patients (70.7% female) with depressive disorder was conducted. Control data from healthy individuals with no psychiatric disorder (n = 72, 26.4% female) and East-Asian subpopulation 1000 Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 67 publications
2
39
0
Order By: Relevance
“…All statistical analyses were conducted using R 3.5.3 ( ). As genetic vulnerabilities in depression risk and antidepressant response have been shown to be different between sexes [ 20 , 21 ], all analyses were conducted on the total population and separately on men and women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All statistical analyses were conducted using R 3.5.3 ( ). As genetic vulnerabilities in depression risk and antidepressant response have been shown to be different between sexes [ 20 , 21 ], all analyses were conducted on the total population and separately on men and women.…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed to uncover genetic markers for predicting non-remission in patients exhibiting poor early improvement using WES data from a depression cohort ( n = 1000) undergoing 12 weeks of antidepressant treatment with a naturalistic design. To decrease the limitation of sample heterogeneity, separate analyses were performed according to sex due to evidence indicating that there are differences between the sexes in terms of the effects of genetic vulnerabilities on depression risk [ 20 ] and antidepressant responses [ 21 ]. To consider the complex effects of multiple variants and their interactions on antidepressant response within genes as functional units, the gene-wise variant burden (GVB) scoring approach reflecting the cumulative contributions of several variants in specific genes [ 22 ] was used in the present analyses instead of polygenic risk scores, which do not yield reliable predictions of antidepressant response [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that the lifetime prevalence of major depressive episodes was higher in females than in males and the onset was earlier in females [ 37 ]. This difference may arise from behavioral characteristics and fundamental genetic reasons [ 38 , 39 ]. In addition, perimenopausal disorder may contribute to the female sex being predictive of MDD, as shown in our model and a previous study [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation may help this understanding. Sex-specific differences in the effects of genetic risk factors on health outcomes have been reported [32] including for mortality rates after injury [33], susceptiblity to immune diseases [34], response to vaccination [35], chronic obstructive pulmonary disease risk [36], basal cell carcinoma [37], cardiometabolic disorders [38,39], and depression [40,41]. Genetic variation in placental tissue has also been shown to impact birth outcomes including large for gestational age [42], birthweight [43,44], and preterm birth [45], but studies to investigate differences in genetic risks by sex or to identify genetic variant associations with placenta size and morphology are lacking.…”
Section: Introductionmentioning
confidence: 99%